Efektivitas Edukasi Aplikasi Permainan Ular Tangga Digital Terhadap Pengetahuan Konsumsi Buah dan Sayur pada Remaja - Rumapea, Lastri Margareth; Kalsum, Ummi; Kasyani Kasyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Fruit and vegetable consumption in Jambi Province in 2018 was still relatively low, due to a lack of knowledge about fruits and vegetables. Knowledge among adolescents can be improved by providing education through digital snake and ladder games. The purpose of this study was to examine the effectiveness of nutrition education through digital snake and ladder game applications on knowledge about fruit and vegetable consumption among adolescents. This quasi-experimental study used a pretest-posttest design with a control group. The sampling technique was proportional random sampling, with 40 treatment groups and 40 control groups. The treatment group (digital snakes and ladders game) was located at SMPN 2 Muaro Jambi, and the control group (leaflet) was located at SMPN 10 Muaro Jambi. The dependent variable was knowledge, measured using a questionnaire. This study used the Paired T Test and Mann-Whitney tests. The average knowledge scores before and after the intervention in the treatment group increased (p-value 0.000). The average knowledge scores before and after the intervention in the control group also increased (p-value 0.016). The average knowledge score after the intervention in the treatment group was higher than that in the control group (p-value 0.003). The digital snakes and ladders game was more effective than the leaflet in improving knowledge about fruit and vegetable consumption among adolescents.